Pharmacokinetic Interactions Between the Fixed‐Dose Combinations of Elvitegravir/Cobicistat/Tenofovir Disoproxil Fumarate/Emtricitabine and Elbasvir/Grazoprevir in Healthy Adult Participants. Issue 7 (7th June 2019) - Feng, Hwa‐Ping; Guo, Zifang; Fandozzi, Christine; Panebianco, Deborah; Caro, Luzelena; Wolford, Dennis; Dreyer, Daniel P.; Valesky, Robert; Martinho, Monika; Rizk, Matthew L.; Iwamoto, Marian; Yeh, Wendy W.
Abstract: Treatment of individuals coinfected with human immunodeficiency virus (HIV) and hepatitis C virus (HCV) requires careful consideration of potential drug‐drug interactions. The pharmacokinetic interaction of the HCV fixed‐dose combination treatment of elbasvir/grazoprevir (EBR/GZR) when coadministered with the fixed‐dose combination HIV treatment of elvitegravir/cobicistat/tenofovir disoproxil fumarate/emtricitabine (EVG/COB/TDF/FTC) was evaluated in 22 healthy adults. In period 1, oral doses of EVG/COB/TDF/FTC (150 mg/150 mg/300 mg/200 mg) were administered once daily for 7 days. In period 2, oral doses of EBR/GZR (50 mg/100 mg) were administered once daily for 10 days. In period 3, oral doses of EVG/COB/TDF/FTC were coadministered with EBR/GZR once daily for 10 days. The pharmacokinetics of EVG/COB/TDF/FTC were not clinically meaningfully altered by concomitant EBR/GZR administration. Geometric mean ratios (90%CIs) for area under the plasma concentration‐time curve from time 0 to 24 hours (AUC0‐24 ) in the presence/absence of EBR/GZR were 1.1 (1.0, 1.2) for elvitegravir; 1.1 (1.0, 1.1) for emtricitabine; 1.2 (1.1, 1.2) for tenofovir; and 1.5 (1.4, 1.6) for cobicistat. In comparison, the AUC0‐24 of elbasvir was ∼2 times higher and the AUC0‐24 of grazoprevir was ∼5 times higher following concomitant administration of EVG/COB/TDF/FTC and EBR/GZR. Geometric mean ratios (90%CI) for AUC0‐24 in the presence/absence of EVG/COB/TDF/FTC were 2.2 (2.0, 2.4) for elbasvir and 5.4 (4.5, 6.4) for grazoprevir. Coadministration of EVG/COB/TDF/FTC and EBR/GZR was generally well tolerated in healthy adults in this study. Nevertheless, because of the increased GZR exposure that occurs with coadministration of EVG/COB/TDF/FTC and EBR/GZR, coadministration of this combination is not recommended in those coinfected with HIV and HCV.